Economic thickness and life cycle cost analysis of insulating layer for the urban district steam heating pipe. (June 2022) - Zhang, Tianhu; Li, Aoqi; Hari, Qiga; Li, Xiaopeng; Rao, Yandi; Tan, Hongying; Du, Shenghua; Zhao, Qingxin
Abstract: The direct buried steam pipeline with effective insulation has great potential application in the district heating systems. In this study, a life cycle cost model for the direct buried steam pipeline was established, and an optimization method was proposed to improve the insulation performance. The influences of insulation material and pipe diameter on the total life cycle cost, economic thickness, energy efficiency, and payback period were analyzed. Under the low-temperature working conditions, the composite insulation scheme composed of high-temperature resistant glass wool (HTRGW) and SiO2 aerogel blanket (SAB) exhibited excellent economic efficiency. Moreover, the life cycle cost and economic thickness show a significant decrease with the increase of pipe diameter, and the economic benefit increased appropriately. When the pipe diameter increased from DN100 to DN700, the life cycle cost was decreased by 351 RMB/m, the economic thickness was decreased by 71 mm, and the economic benefit was increased by 30 RMB/m. Under the high-temperature working conditions, aluminium silicate wool (ASW) was involved in the insulation scheme. When the HTRGW/SAB was adopted instead of HTRGW/ASW, the total life cycle cost was reduced by 133–224 RMB/m, the economic thickness was reduced by 52–55 mm, and the economic efficiency was increased by 17–22 RMB/(m·a).